Crosstalk Between NDP52 and LUBAC in Innate Immune Responses, Cell Death, and Xenophagy - Miyashita, Hirohisa; Oikawa, Daisuke; Terawaki, Seigo; Kabata, Daijiro; Shintani, Ayumi; Tokunaga, Fuminori (Frontiers in Immunology, 2021)
Nuclear dot protein 52 kDa (NDP52, also known as CALCOCO2) functions as a selective autophagy receptor. The linear ubiquitin chain assembly complex (LUBAC) specifically generates the N-terminal Met1-linked linear ubiquitin chain, and regulates innate immune responses, such as nuclear factor-κB (NF-κB), interferon (IFN) antiviral, and apoptotic pathways. Although NDP52 and LUBAC cooperatively regulate bacterial invasion-induced xenophagy, their functional crosstalk remains enigmatic. Here we show that NDP52 suppresses canonical NF-κB signaling through the broad specificity of ubiquitin-binding at the C-terminal UBZ domain. Upon TNF-α-stimulation, NDP52 associates with LUBAC through the HOIP subunit, but does not disturb its ubiquitin ligase activity, and has a modest suppressive effect on NF-κB activation by functioning as a component of TNF-α receptor signaling complex I. NDP52 also regulates the TNF-α-induced apoptotic pathway, but not doxorubicin-induced intrinsic apoptosis. A chemical inhibitor of LUBAC (HOIPIN-8) cancelled the increased activation of the NF-κB and IFN antiviral pathways, and enhanced apoptosis in NDP52-knockout and -knockdown HeLa cells. Upon Salmonella-infection, colocalization of Salmonella, LC3, and linear ubiquitin was detected in parental HeLa cells to induce xenophagy. Treatment with HOIPIN-8 disturbed the colocalization and facilitated Salmonella expansion. In contrast, HOIPIN-8 showed little effect on the colocalization of LC3 and Salmonella in NDP52-knockout cells, suggesting that NDP52 is a weak regulator in LUBAC-mediated xenophagy. These results indicate that the crosstalk between NDP52 and LUBAC regulates innate immune responses, apoptosis, and xenophagy.